ادارة المخاطر البيئية والتنمية المستدامة دراسة مدينة الجميل (Comprehensive Journal of Science, 2025)
The aim of this paper to recognize the environmental hazards which threating the city develop and sustainability and how to overcome on these problems.The paper studied Al jemel city as a case studyassists the case of the city its natural resources and environmental threating facing the city sustainability and developmentThe paper came with conclusion and recommendation
Keywords: Hazards , environment , development and natural resources , sustainability , pollution